Positive electrode active material, method for producing same, and use thereof

CN121394386BActive Publication Date: 2026-10-23CHONGQING TALENT NEW ENERGY CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511571099.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-10-30
Publication Date
2026-10-23
Estimated Expiration
2045-10-30

AI Technical Summary

Technical Problem

[0003]但是上述钠离子电池同时也存在一些弊端,例如在电芯充满电的过程中,磷酸锰铁钠材料中的Mn3+会发生歧化反应,生成Mn2+和Mn4+,同时Fe3+会通过自放电还原成Fe2+,Mn2+和Fe2+不仅会与电解液发生副反应而影响电解液的性能,而且高温下Mn2+和Fe2+的溶出速率加快,溶出后的Mn2+和Fe2+会通过扩散侵蚀石墨负极的SEI膜,会使负极SEI膜不断损耗,导致电芯的整体活性锂损失,电芯的高温循环性能和高温存储性能受到不可逆的损伤,上述弊端也存在于其它的碱金属离子电池中

Benefits of technology

[0004]本申请旨在至少在一定程度上解决相关技术中的技术问题之一。为此,本申请提出一种正极活性材料及其制备方法、应用,使用该正极活性材料的钠离子电池具有优异的高温循环性能和高温存储性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application belongs to the technical field of batteries, and discloses a positive electrode active material, a preparation method and application thereof. The positive electrode active material comprises an alkali metal iron manganese phosphate and an additive. The additive comprises at least one of a metal organic framework material and a covalent organic framework material. The alkali metal iron manganese phosphate comprises at least one of sodium iron manganese phosphate and potassium iron manganese phosphate. An alkali metal ion battery adopting the positive electrode active material has excellent high-temperature storage performance and high-temperature cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of battery technology, specifically relating to positive electrode active materials and their preparation methods and applications, and more specifically relating to positive electrode active materials and their preparation methods, positive electrode sheets, alkali metal ion batteries, and electrical devices. Background Technology

[0002] Among various applicable energy storage technologies, alkali metal ion batteries have become a research hotspot in recent years as a general electrochemical energy storage method for both portable and large-scale power storage. Among them, sodium iron manganese phosphate batteries are a common type of sodium-ion battery, often referred to as polyanion sodium batteries. They have advantages such as low cost and good room-temperature cycling performance, and are widely used in 3C digital products and two-wheeled vehicles.

[0003] However, the aforementioned sodium-ion batteries also have some drawbacks. For example, during the process of fully charging the cell, the Mn in the sodium manganese iron phosphate material... 3+ A disproportionation reaction will occur, producing Mn. 2+ and Mn 4+ At the same time, Fe 3+ It will be reduced to Fe through self-discharge. 2+ Mn 2+ and Fe 2+ Not only will it undergo side reactions with the electrolyte, affecting the electrolyte's performance, but Mn will also... 2+ and Fe 2+ The dissolution rate is accelerated, and the dissolved Mn 2+ and Fe 2+ Diffusion erosion of the SEI film on the graphite anode leads to continuous wear and tear on the SEI film, resulting in an overall loss of active lithium in the cell. This causes irreversible damage to the cell's high-temperature cycle performance and high-temperature storage performance. These drawbacks also exist in other alkali metal-ion batteries. Therefore, solving these problems in alkali metal-ion batteries is currently one of the challenges. Summary of the Invention

[0004] This application aims to at least partially address one of the technical problems in related technologies. To this end, this application proposes a positive electrode active material, its preparation method, and its application. Sodium-ion batteries using this positive electrode active material exhibit excellent high-temperature cycle performance and high-temperature storage performance.

[0005] In a first aspect of this application, a positive electrode active material is proposed, comprising an alkali metal iron manganese phosphate salt and additives; The additives include at least one of metal-organic framework materials and covalent organic framework materials; The alkali metal iron manganese phosphate salt includes at least one of the alkali metals sodium iron manganese phosphate and potassium iron manganese phosphate.

[0006] In this application, the adsorption properties of covalent organic framework materials (MoFs materials) and metal-organic framework materials (MoFs materials) can be utilized to effectively adsorb Mn dissolved from alkali metal ion batteries (sodium iron manganese phosphate batteries or potassium iron manganese phosphate batteries). 2+ and Fe 2+ Specifically, CoFs materials can adsorb Mn 2+ This is mainly because CoFs materials have regular one-dimensional nanopores, which can be used for Mn 2+ Provides efficient diffusion and enrichment space, Mn 2+ Preliminary enrichment can be achieved by physical trapping Fe within one-dimensional nanopores through van der Waals forces; furthermore, MoFs materials can adsorb Fe due to the synergistic effect of their structural characteristics and surface chemical modifications. 2+ Specifically, MoFs materials have high specific surface area and porosity, which can be used to enhance the properties of Fe. 2+ It provides the physical space for diffusion and enrichment, and achieves initial adsorption through van der Waals forces.

[0007] In some embodiments, the additive includes metal-organic framework materials and covalent organic framework materials. This helps to further improve the control of Fe... 2+ and Mn 2+ Effective adsorption.

[0008] In some embodiments, the additive satisfies at least one of the following conditions: The metal-organic framework material includes Co6(BPDC)6; The covalent organic framework material includes COF-7. Co6(BPDC)6 has a high specific surface area and porosity, while COF-7 has regular one-dimensional nanopores, which helps to achieve Fe... 2+ and Mn 2+ Effective adsorption.

[0009] In some embodiments, the additive satisfies at least one of the following conditions: The specific surface area of ​​the metal-organic framework material is >1000 m². 2 / g; The pore size of the metal-organic framework material is 0.8 nm-1.3 nm; The covalent organic framework material has nanopores on its surface, with pore sizes ranging from 1.63 nm to 4.80 nm. This facilitates the control of Fe... 2+ and Mn 2+ Effective adsorption.

[0010] In some embodiments, the positive electrode active material satisfies at least one of the following conditions: The content of the alkali metal iron manganese phosphate in the positive electrode active material is 94wt%~99wt%; The metal-organic framework material has a content of 0.5 wt% to 3 wt% in the positive electrode active material; The covalent organic framework material is present in the positive electrode active material at a content of 0.5 wt% to 3 wt%. This helps to obtain a positive electrode active material with a balance of adsorption performance, cycle stability, and rate performance.

[0011] In some embodiments, at least one of the following conditions is met: The particle size of the alkali metal iron manganese phosphate is 1.1 μm to 1.6 μm; The D50 particle size of the metal-organic framework material is 90nm-300nm; The D50 particle size of the covalent organic framework material is 80 nm-500 nm. This helps to obtain a structurally stable positive electrode active material with excellent adsorption performance.

[0012] In some embodiments, the alkali metal iron manganese phosphate includes Mn a Fe b Al c W d Nb e C f PO4; Where 0 < a < 1, 0 < b < 1, 0 ≤ c < 1, 0 ≤ d < 1, 0 ≤ e < 1, 0 ≤ f < 1, and M represents sodium or potassium. This helps to further improve the various properties of the positive electrode active material.

[0013] In a second aspect of this application, a method for preparing a positive electrode active material is provided, comprising: By mixing alkali metal iron-manganese phosphate salts with additives, a positive electrode active material is obtained. Thus, a positive electrode active material with adsorption properties can be prepared through simple mixing.

[0014] In some embodiments, the mixing is performed at a rotation speed of 100 rpm to 200 rpm for 1 to 2 hours. This helps to obtain a positive electrode active material with better uniformity.

[0015] In a third aspect of this application, a positive electrode sheet is proposed, comprising the aforementioned positive electrode active material. Therefore, alkali metal ion batteries using this positive electrode sheet exhibit excellent high-temperature storage performance and high-temperature cycling performance.

[0016] In a fourth aspect of this application, an alkali metal ion battery is proposed, comprising the aforementioned positive electrode active material or the aforementioned positive electrode sheet. Therefore, this alkali metal ion battery exhibits excellent high-temperature storage performance and high-temperature cycle performance.

[0017] In a fifth aspect of this application, an electrical device is proposed, comprising the aforementioned positive electrode active material, the aforementioned positive electrode sheet, or the aforementioned alkali metal ion battery. Therefore, this electrical device exhibits excellent high-temperature storage performance and high-temperature cycling performance. Detailed Implementation

[0018] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and intended to explain this application, and should not be construed as limiting this application.

[0019] As mentioned earlier, Mn will dissolve after an alkali metal ion battery is fully charged. 2+ and Fe 2+ Furthermore, it can erode the SEI film of the graphite anode through diffusion, thereby affecting the battery's high-temperature storage and high-temperature cycle performance. Based on this, the inventors considered introducing an additive into the alkali metal iron-manganese phosphate salt of the positive electrode active material to adsorb dissolved Mn, without affecting other battery performance characteristics. 2+ and Fe 2+ To a certain extent, avoid Mn 2+ and Fe 2+ Erosion of the SEI film on the graphite anode improves the high-temperature performance of alkali metal ion batteries.

[0020] Therefore, in a first aspect, this application proposes a positive electrode active material comprising an alkali metal iron manganese phosphate salt and an additive; the additive comprises at least one of a metal-organic framework material and a covalent organic framework material; the alkali metal iron manganese phosphate salt comprises at least one of sodium iron manganese phosphate and potassium iron manganese phosphate.

[0021] In this application, the adsorption properties of covalent organic framework materials (MoFs materials) and metal-organic framework materials (MoFs materials) can be utilized to effectively adsorb Mn dissolved from alkali metal ion batteries. 2+ and Fe 2+ Specifically, CoFs materials can adsorb Mn 2+ This is mainly because CoFs materials have regular one-dimensional nanopores, which can be used for Mn 2+ Provides efficient diffusion and enrichment space, Mn 2+ Preliminary enrichment can be achieved by physical trapping Fe within one-dimensional nanopores through van der Waals forces; furthermore, MoFs materials can adsorb Fe due to the synergistic effect of their structural characteristics and surface chemical modifications. 2+ Specifically, MoFs materials have high specific surface area and porosity, which can be used to enhance the properties of Fe. 2+ The diffusion and enrichment of Mn in iron manganese phosphate provides the physical space, and initial adsorption is achieved through van der Waals forces. Meanwhile, Mn in iron manganese phosphate... 3+ Mn generated by the disproportionation reaction 4+It can also provide a certain capacity to the battery, and the above-mentioned additives all have excellent conductivity, which helps to further improve the conductivity of the positive electrode active material.

[0022] In some embodiments, the additives include metal-organic framework materials and covalent organic framework materials. Through the synergistic effect of MoFs and CoFs materials, Mn dissolved from alkali metal-ion batteries can be partially absorbed. 2+ and Fe 2+ Adsorption helps to further improve the high-temperature performance of alkali metal ion batteries.

[0023] In some embodiments, the alkali metal iron manganese phosphate includes Mn a Fe b Al c W d Nb e C f PO4, where 0 < a < 1, 0 < b < 1, 0 ≤ c < 1, 0 ≤ d < 1, 0 ≤ e < 1, 0 ≤ f < 1, and M is sodium or potassium. Doping alkali metal iron-manganese phosphates with metal ions (such as W, Nb, etc.) can alter their crystal structure, increase electron delocalization, reduce material resistance, and improve conductivity, thereby accelerating electron transport during battery charging and discharging and improving charging and discharging efficiency. Simultaneously, introducing an appropriate amount of carbon source can increase the active sites of the material, promote electrochemical reactions, and further improve battery storage performance.

[0024] In some embodiments, the content of the alkali metal iron-manganese phosphate in the positive electrode active material is 94wt%~99wt%, specifically, it can be 94wt%, 95wt%, 96wt%, 97wt%, 98wt%, 99wt%, etc. The content of the alkali metal iron-manganese phosphate in the positive electrode active material within the above range can basically ensure the diffusion and migration of alkali metal ions during battery charging and discharging, thereby contributing to the positive electrode active material having good cycle stability and rate performance. Furthermore, after multiple charge-discharge cycles, the battery's capacity retention rate is high, which helps to extend the battery's lifespan. This essentially avoids the problem of limited ion and electron transport channels inside the active material due to excessively low alkali metal iron-manganese phosphate content, which would prevent alkali metal ions from rapidly inserting and de-inserting under high current charging and discharging conditions, thus affecting the battery's cycle performance and rate performance.

[0025] In some embodiments, the particle size of the alkali metal iron manganese phosphate is 1.1 μm to 1.6 μm, specifically 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, etc. The particle size of the alkali metal iron manganese phosphate is within the above range, which can basically ensure that the particles of the alkali metal iron manganese phosphate have a suitable pore structure, which is conducive to the smooth insertion and extraction of alkali metal ions during charging and discharging. At the same time, it helps to ensure that the positive electrode active material and the electrolyte have a suitable contact area, which can ensure that there are enough active sites to participate in the electrochemical reaction, and will not cause too many side reactions due to excessive specific surface area.

[0026] In some embodiments, the content of the MoFs material in the positive electrode active material is 0.5wt%~3wt%, specifically, it can be 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, etc. The content of the MoFs material in the positive electrode active material within the above range can basically ensure that it is sufficient to meet the Fe dissolved from the alkali metal ion battery. 2+ Provides ample space for diffusion and enrichment, effectively adsorbing Fe 2+ To avoid Fe 2+ It moves freely within the battery system, thereby avoiding Fe 2+ This approach mitigates the adverse effects on battery high-temperature performance, ensuring stable battery operation under high-temperature conditions. It largely avoids the adsorption of Fe caused by excessively low MoFs content in the positive electrode active material. 2+ Insufficient capacity and excessive content of alkali metal iron manganese phosphate active ingredients lead to a decrease in the content of these active ingredients, thereby reducing the overall energy density and specific capacity of the battery.

[0027] In some embodiments, the MoFs material includes Co6(BPDC)6. As a type of MoFs material, Co6(BPDC)6 possesses the common characteristics of high specific surface area and porosity of MoFs materials, which can facilitate the dissolution of Fe from alkali metal ion batteries. 2+ Providing ample space for diffusion and enrichment facilitates the control of Fe through van der Waals forces. 2+ The initial adsorption of Fe inhibits Fe. 2+ It can move freely within the battery system, improving the high-temperature performance of alkali metal ion batteries.

[0028] In some embodiments, the specific surface area of ​​the MoFs material is >1000 m². 2 / g, specifically 1100 m 2 / g, 1500 m 2 / g、2000 m 2 / g、2500 m 2 / g, etc., the specific surface area of ​​MoFs materials within the above range can basically ensure that the surface of MoFs materials has a rich porous structure, which can facilitate the dissolution of Fe in alkali metal ion batteries. 2+ Providing ample physical space for diffusion and enrichment facilitates the control of Fe through van der Waals forces. 2+ Preliminary adsorption reduces Fe 2+ Free movement within the battery system reduces its adverse effects on battery performance.

[0029] In some embodiments, the pore size of the MoFs material is 0.8 nm-1.3 nm, specifically 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm, 1.3 mm, etc. A porosity within the above range for the MoFs material helps to further improve the control of Fe. 2+ Preliminary adsorption reduces Fe 2+ Free movement within the battery system.

[0030] In some embodiments, the D50 particle size of the MoFs material is 90 nm-300 nm, specifically 90 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, etc. A particle size within this range generally ensures that the MoFs material has a high specific surface area and abundant pore structure, which is beneficial for adsorbing Fe. 2+ Provide ample space.

[0031] In some embodiments, the content of CoFs material in the positive electrode active material is 0.5wt%~3wt%, specifically, it can be 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, etc. The content of CoFs material in the positive electrode active material within the above range can basically ensure the removal of Mn dissolved from the alkali metal ion battery. 2+ Effective adsorption, reducing Mn 2+ The free movement of CoFs within the battery system largely ensures the stability of the battery's high-temperature performance. It also largely avoids the adsorption of Mn caused by excessively low CoFs content in the positive electrode active material. 2+ Insufficient capacity and excessive content of alkali metal iron manganese phosphate active ingredients lead to a decrease in the content of these active ingredients, thereby reducing the overall energy density and specific capacity of the battery.

[0032] In some embodiments, the CoFs material includes COF-7, which has regular one-dimensional nanopores capable of facilitating the dissolution of Mn from alkali metal ion batteries. 2+ Provides efficient diffusion and enrichment space, Mn 2+Mn can be initially enriched by being physically trapped inside one-dimensional nanopores through van der Waals forces, thereby reducing its concentration. 2+ Free movement within the battery system prevents issues such as performance degradation caused by ionization.

[0033] In some embodiments, the CoFs material has nanopores with a pore size of 1.63 nm to 4.8 nm, specifically, 1.63 nm, 2.0 nm, 2.5 nm, 3.0 nm, 3.5 nm, 4.0 nm, 4.5 nm, 4.8 nm, etc. The pore size of the nanopores within the above range allows for the interaction of Mn dissolved from the alkali metal ion battery. 2+ Size adaptation helps for Mn 2 + Provides efficient diffusion and enrichment space, Mn 2+ It can smoothly enter the pores and be trapped inside the nanopores by van der Waals forces, thus achieving the control of Mn. 2+ Adsorption of Mn reduces 2+ Free movement within the battery system, thereby avoiding Mn 2+ The SEI film on the graphite anode is eroded, affecting the high-temperature performance of alkali metal ion batteries.

[0034] In some embodiments, the D50 particle size of the CoFs material is 80 nm-500 nm, specifically 80 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, etc. A particle size within the above range generally ensures that the CoFs material has a certain number of nanopores, which is beneficial for adsorbing Mn. 2+ Provide ample space.

[0035] In a second aspect of this application, a method for preparing the aforementioned positive electrode active material is provided, comprising: mixing an alkali metal iron manganese phosphate salt with an additive to obtain the positive electrode active material.

[0036] Specifically, the alkali metal iron-manganese phosphate salt and additives are mixed at a speed of 100 rpm to 200 rpm for 1 to 2 hours to ensure uniform mixing. Mixing speeds can be 100 rpm, 110 rpm, 120 rpm, 130 rpm, 140 rpm, 150 rpm, 160 rpm, 170 rpm, 180 rpm, 190 rpm, 200 rpm, etc. Mixing speeds within these ranges provide moderate stirring power, which can basically ensure sufficient dispersion of the alkali metal iron-manganese phosphate salt and additives in the mixed system.

[0037] Furthermore, the mixing time can be 1 hour, 1.2 hours, 1.5 hours, 1.8 hours, 2 hours, etc. The above mixing time can further ensure that the alkali metal iron manganese phosphate salt and the additive are mixed evenly, which can basically avoid the problems of uneven dispersion caused by a short mixing time and increased time cost caused by an excessively long mixing time.

[0038] In some embodiments, alkali metal iron manganese phosphate (MMn) a Fe b Al c W d Nb e C f PO4 is prepared using a solid-state process, the preparation method of which includes: S10: Mix alkali metal, manganese source, iron source, phosphorus source and optional dopant to obtain a first mixture.

[0039] In this step, for example, sodium, manganese, iron, and phosphorus sources are mixed in a molar ratio of Na : (Mn+Fe) : P = 1 :1 :1, wherein the molar ratio of manganese to iron is 6 : 4. That is, 400g of sodium hydroxide, 1375g of manganese tetroxide, 720g of ferrous oxalate, 980g of phosphoric acid, 10g of niobium oxide, and 5g of tungsten oxide are weighed and placed in a container for dry mixing. Dry mixing can be carried out at a speed of 50rpm~150rpm for 0.5h~1h. After dry mixing, 5 wt% of carbon source, i.e., 197g of glucose, is added, along with 3.5kg of ultrapure water for wet mixing. Wet mixing can be carried out at a speed of 50rpm~150rpm for 5h~8h to obtain the first mixture.

[0040] S20: The first mixture is subjected to a first ball milling and drying to obtain a first ball milled product.

[0041] In this step, for example, the first mixture is placed in a ball mill and ball-milled for 10 to 12 hours. After the ball milling is completed, it is dried at 100°C to 150°C to remove moisture, and then the dried mixture is mixed using a planetary mixer, specifically at a speed of 150 rpm to 200 rpm for 6 to 10 hours, to obtain the first ball-milled product.

[0042] In some embodiments, the particle size D50 of the first ball-milled product is 1.2 μm to 1.3 μm, specifically, it can be 1.2 μm, 1.22 μm, 1.24 μm, 1.26 μm, 1.28 μm, 1.3 μm, etc. The particle size of the first ball-milled product within the above range helps to obtain sodium iron manganese phosphate with a particle size range of 1.1 μm to 1.6 μm through subsequent steps. This can basically ensure that the prepared sodium iron manganese phosphate has a suitable pore structure, which is conducive to the smooth insertion and extraction of sodium ions during charging and discharging. At the same time, it helps to ensure that the positive electrode active material and the electrolyte have a suitable contact area, which can ensure that there are enough active sites to participate in the electrochemical reaction, and will not cause too many side reactions due to excessive specific surface area.

[0043] S30: The first ball-milled product is subjected to low-temperature sintering to obtain a sintered product.

[0044] In this step, the first ball-milled product obtained above is sintered at low temperature in an inert atmosphere (nitrogen or argon) to allow for preliminary decomposition of the first ball-milled product and prevent manganese oxidation. Specifically, sintering can be performed at 450℃~550℃ for 10h~15h to obtain a first-burned product.

[0045] S40: The first sintered product is subjected to high-temperature sintering to obtain the second sintered product.

[0046] In this step, the product from the first calcination is heated from 450℃~550℃ to 800℃~850℃ and sintered for 15h~20h, and then cooled to below 50℃ to obtain the product from the second calcination.

[0047] In some embodiments, the heating rate is 4°C / min to 6°C / min, specifically 4°C / min, 5°C / min, 6°C / min, etc. Heating rates within this range help prevent distortion of sodium iron manganese phosphate crystals. Further, the cooling rate is 10°C / min to 15°C / min.

[0048] S50: The calcined product is subjected to a second ball milling to obtain a second ball-milled product. In this step, the calcined product is ball-milled, specifically at a speed of 200 rpm to 400 rpm for 3-5 hours.

[0049] In some embodiments, the particle size D50 of the second ball-milled product is 1.5 μm to 1.7 μm, specifically, it can be 1.5 μm, 1.55 μm, 1.6 μm, 1.65 μm, 1.7 μm, etc. The particle size of the second ball-milled product being within the above range helps to obtain sodium iron manganese phosphate with a particle size range of 1.1 μm to 1.6 μm through subsequent steps.

[0050] S60: The second ball-milled product, along with optional dopants and coating agents, is mixed and sintered at low temperature to obtain the sodium manganese iron phosphate.

[0051] In this step, for example, 5 wt% of carbon source, namely 197g of glucose and 15g of aluminum fluoride, are added to the second ball milling product. The mixture is then dry-mixed at 150rpm~200rpm for 8h~10h using a planetary mixer. After the mixture is homogeneous, it is sintered at 450℃~550℃ for 6h~8h to enhance its conductivity, thereby obtaining sodium iron manganese phosphate.

[0052] In some embodiments, an exemplary method for preparing MoFs materials (with Co6(BPDC)6 as the ligand) includes: A10: Preparation of Mixture A: Dissolve 56g of zirconium phosphate (Zr(HPO4)2) and 2.6g of CoCl2 in 500mL of N,N-dimethylformamide (DMF), then add 150mL of hydrochloric acid and ultrasonically disperse until uniform. A20: Preparation of Mixture B: Dissolve 150 mL of 4,4'-biphenyldicarboxylic acid (BPDC) in 700 mL of DMF by magnetic stirring.

[0053] A30: Reaction and Crystallization: Mixture A and mixture B are mixed and then transferred to a polytetrafluoroethylene reactor. The mixture is reacted in an oven at 110°C for 24 hours to produce a pinkish-purple precipitate.

[0054] A40: Post-processing: The above-mentioned pinkish-purple precipitate was separated by vacuum filtration. The filtered product was washed three times with DMF and ethanol respectively, and then vacuum dried at 100℃ for 15 hours to obtain cobalt-based UiO-67 powder. The powder was then ground in a mortar for 10 minutes to obtain MoFs material with the target particle size.

[0055] In some embodiments, exemplary, CoFs materials (COF-7, monomer is C) 26 H 18 The preparation methods of ) include: B10: Preparation of mixed solvent: Mix mesitylene and 1,4-dioxane at a volume ratio of 1:1.

[0056] B20: Reaction: 100g of thioether functionalized monomer (2,5-diethylthio-terephthalohydrazide) and 100g of crosslinking monomer (trimethylammonium pyromelliticate) were added to a 300 mL pressure-resistant tube, and 20 mL of mixed solvent was injected. The tube was sonicated for 20 minutes to disperse the monomer evenly. Then, 15 mL of acetic acid was added as a catalyst. At the same time, nitrogen was introduced to replace the oxygen in the pressure-resistant tube and the tube was sealed. The pressure-resistant tube was placed in a 120℃ oven for 48 hours to generate an orange-red precipitate.

[0057] B30: Post-processing: After cooling the above orange-red precipitate to room temperature, filter it and wash it three times with anhydrous ethanol and tetrahydrofuran respectively. Dry it under vacuum at 120℃ for 15 hours to obtain orange-red COF-7 powder. Grind it in a mortar for 10 minutes to obtain CoFs material with the target particle size.

[0058] In a third aspect of this application, a positive electrode sheet is provided, comprising the aforementioned positive electrode active material. Specifically, the positive electrode sheet includes a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector, the positive electrode material layer comprising a positive electrode active material.

[0059] In some embodiments, the positive electrode material layer includes the aforementioned positive electrode active material and auxiliary material. Specifically, the positive electrode active material includes sodium iron manganese phosphate (NaMn) prepared in the aforementioned steps. a Fe b Al c W d Nb e C f PO4 and additives are the source of battery capacity; auxiliary materials include conductive agents, binders, dispersants, etc., which help to obtain a positive electrode material layer with excellent conductivity. In some embodiments, exemplary, the preparation method of the above-mentioned positive electrode sheet includes: firstly, mixing the positive electrode active material, conductive agent, binder, and dispersant in a mass ratio of 96.8:1.5:1.5:0.2; firstly, dry mixing the mixture, then adding an appropriate amount of solvent for wet mixing to obtain a positive electrode slurry, controlling the solid content of the positive electrode slurry to be 65%; further, coating the positive electrode slurry onto a 14μm thick carbon-coated aluminum foil (wherein the aluminum foil thickness is 12 micrometers, and each side of the aluminum foil is coated with a 1-micrometer thick carbon layer), so that the double-sided areal density of the positive electrode sheet is 4 mg / cm³. 2 After drying at 100℃~120℃, the dried positive electrode sheet is obtained. Finally, the dried positive electrode sheet is rolled to achieve a compaction density of 2.10 g / cm³. 3 ~2.30g / cm 3 The prepared positive electrode sheet is die-cut according to the cell size and placed in a nitrogen oven at 100℃ for later use.

[0060] In a fourth aspect of this application, an alkali metal ion battery is proposed, comprising the aforementioned positive electrode active material or positive electrode sheet. Therefore, this alkali metal ion battery exhibits excellent high-temperature storage performance and high-temperature cycling performance.

[0061] In some embodiments, the above-mentioned alkali metal ion battery further includes a negative electrode, an electrolyte, and a separator. The positive electrode, negative electrode, and separator are all immersed in the electrolyte. During the charging and discharging process of the battery, active ions are inserted and extracted back and forth between the positive and negative electrodes. The electrolyte plays the role of conducting ions between the positive and negative electrodes. The separator is disposed between the positive and negative electrodes and mainly plays the role of preventing short circuits between the positive and negative electrodes, while allowing active ions to pass through.

[0062] In some embodiments, the negative electrode sheet may include a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector. As an example, the negative electrode active material layer may include a negative electrode material, a thickener, a conductive agent, and a binder.

[0063] Specifically, the negative electrode current collector can be a metal foil, for example, copper foil. The negative electrode material can include carbon-based materials, silicon-based materials, tin-based materials, etc. The binder in the negative electrode material layer can include, but is not limited to, at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethyl methacrylate (PMAA), and carboxymethyl chitosan (CMCS). The conductive agent in the negative electrode material layer can include, but is not limited to, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0064] In some embodiments, the separator may be a separator known in the art that can be used in lithium-ion batteries and is stable to the electrolyte used, such as a polyethylene separator, a polypropylene separator, a polyethylene / polypropylene composite separator, etc.

[0065] In some embodiments, an exemplary method for preparing a negative electrode sheet includes: homogenizing a mixture of hard carbon, conductive agent, and binder in a mass ratio of 96.5:1.0:2.5; first, dry-mixing the mixture, then adding an appropriate amount of solvent for wet mixing to obtain a negative electrode slurry, controlling the solid content of the negative electrode slurry to be 55%; then, coating the negative electrode slurry onto a 6 μm thick copper foil to achieve a double-sided areal density of 13 mg / cm² for the negative electrode sheet. 2 The negative electrode sheet is dried at 80℃. Finally, the dried negative electrode sheet is rolled to achieve a compaction density of 1.50 g / cm³. 3 Then, the rolled negative electrode sheet is die-cut according to the cell size and placed in a nitrogen oven at 90℃ for later use.

[0066] In some embodiments, exemplary, the above-mentioned method for preparing an alkali metal ion battery includes: using a stacking process where the negative electrode sheet needs to be one more than the positive electrode sheet, stacking the electrodes in the manner of separator, negative electrode sheet, separator, positive electrode sheet, separator, and negative electrode sheet, and after hot pressing, welding tabs, and encapsulation, controlling the moisture content to be below 400 ppm, and injecting liquid according to the designed capacity, with an injection coefficient of 4.0 g / Ah.

[0067] In a fifth aspect of this application, an electrical device is proposed, comprising the aforementioned positive electrode active material, the aforementioned positive electrode sheet, or the aforementioned alkali metal ion battery. Therefore, this electrical device exhibits excellent high-temperature storage performance and high-temperature cycling performance.

[0068] In some embodiments, the specific type of electrical device is not particularly limited and can be any device that uses an alkali metal ion battery as a power source or energy storage unit. Examples of electrical devices include, but are not limited to, electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), mobile terminals (e.g., mobile phones, laptops, game consoles, wearable devices, etc.), drones, aerospace equipment, satellites, ships, energy storage systems, and so on.

[0069] It is understandable that, in addition to the sodium-ion battery mentioned above, the electrical device also includes other necessary structures and components, all of which can be made with reference to conventional technologies, such as electric vehicles, which may include the body, chassis, tires, navigation system, radar system, steering system, braking system, lubrication system, cooling system, driving system, etc., which will not be described in detail here.

[0070] The present application will now be described with reference to specific embodiments. It should be noted that these embodiments are merely descriptive and do not limit the present application in any way. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in the art or in accordance with the product manual.

[0071] Example 1 The sodium-ion battery was prepared according to the preparation method in this application, as follows: Preparation of positive electrode active material: A planetary mixer was used to mix sodium iron manganese phosphate (NaFe) according to the following formula: 0.5 Mn 0.5 The positive electrode active material is obtained by mixing the materials with a mass ratio of PO4:MoFs and CoFs of 96:2:2 at a speed of 150 r / min for 1 hour. Preparation of the positive electrode sheet: The positive electrode active material, conductive agent, binder, and dispersant were mixed in a mass ratio of 96.8:1.5:1.5:0.2. The mixture was first dry-mixed, then wet-mixed with an appropriate amount of solvent to obtain a positive electrode slurry. The solid content of the positive electrode slurry was controlled to be 65%. Further, the positive electrode slurry was coated onto a 14μm thick carbon-coated aluminum foil (where the aluminum foil thickness was 12 micrometers, and each side of the aluminum foil was coated with a 1-micrometer thick carbon layer), resulting in a double-sided areal density of 40 mg / cm³ for the positive electrode sheet. 2 After drying at 100℃~120℃, the dried positive electrode sheet is obtained. Finally, the dried positive electrode sheet is rolled to achieve a compaction density of 2.30 g / cm³. 3 The prepared positive electrode sheet is die-cut according to the cell size and placed in a nitrogen oven at 100℃ for later use. Preparation of the negative electrode sheet: A slurry was prepared by mixing hard carbon, conductive agent, and binder in a mass ratio of 96.5:1.0:2.5. The mixture was first dry-mixed, and then wet-mixed with an appropriate amount of solvent to obtain the negative electrode slurry. The solid content of the negative electrode slurry was controlled to be 55%. Then, the negative electrode slurry was coated onto a 6μm thick copper foil to achieve a double-sided areal density of 13mg / cm². 2 The negative electrode sheet is dried at 80℃. Finally, the dried negative electrode sheet is rolled to achieve a compaction density of 1.50 g / cm³. 3 Then, the rolled negative electrode sheet is die-cut according to the cell size and placed in a nitrogen oven at 90℃ for later use. Sodium-ion battery assembly: A stacking process is used, requiring one more negative electrode than positive electrode. The number of electrodes is calculated based on a design capacity of 1Ah. The electrodes are stacked in the following order: separator, negative electrode, separator, positive electrode, separator, negative electrode. After hot pressing, tab welding, and encapsulation, the moisture content is controlled below 400ppm. Electrolyte is injected according to the design capacity, with an injection coefficient of 4.0g / Ah.

[0072] Examples 2-8 Same as Example 1, the main differences are shown in Table 1.

[0073] Comparative Example 1 Same as Example 1, the main differences are shown in Table 1.

[0074] Detection methods 25℃ Cyclic Test: At 25℃, charge to 4.2V with 1C (C=1A) constant current and constant voltage (0.05C), discharge to 2.5V with 1C, cycle 3 times, calibrate the capacity C0, and then perform 1C0CCCV charge / 1C0 discharge 25℃ cyclic test according to the calibrated C0. 45℃ Cyclic Test: At 45℃, charge to 4.2V with 1C (C=1A) constant current and constant voltage (0.05C), discharge to 2.5V with 1C, cycle 3 times, calibrate the capacity C1, and then perform 1C1CCCV charge / 1C1 discharge 45℃ cyclic test according to the calibrated C1. 60℃ High Temperature Storage Test: At 25℃, charge the battery to 4.2V using 1C (C=1A) constant current and constant voltage (0.05C), then discharge it to 2.5V, cycle 3 times, and calibrate the capacity C2. Charge the battery to 4.2V using 1C2 constant current and constant voltage (0.05C), then place the battery in a 60℃ high temperature oven and let it stand for 60 days. After that, discharge the battery at 25℃. The discharge capacity D1 is the residual capacity. Charge the battery to 4.2V using 1C2 constant current and constant voltage (0.05C), then discharge it to 2.5V, cycle 3 times, and the discharge capacity D2 of the third cycle is the recovery capacity.

[0075] Gas production test: The gas production before and after the test was measured using the water displacement method; Mn and Fe dissolution values: After the disassembly and testing of the empty battery, the metal dissolution of the negative electrode was tested using the ICP-MS method. The tested elements included Mn and Fe.

[0076] Table 1

[0077] Conclusion: Examples 1-6 involved varying the mass ratio of sodium iron manganese phosphate:MoFs:CoFs in the positive electrode active material, and all these ratios were within the limits specified in this application. The sodium-ion batteries using the positive electrode active materials from Examples 1-6 exhibited excellent performance, such as low Mn and Fe dissolution values ​​measured at 45°C and 60°C, indicating that the MoFs and CoFs materials can effectively adsorb the Mn dissolved during battery operation. 2+ and Fe 2+ Examples 7 and 8 respectively introduced only MoFs or CoFs materials into the positive electrode active material. It can be seen that the performance of the sodium-ion battery decreased compared to Examples 1-6. In Comparative Example 1, the positive electrode active material was sodium manganese iron phosphate, without the introduction of MoFs or CoFs materials. It can be seen that the performance of the sodium-ion battery was poor, such as extremely high Mn and Fe dissolution values ​​and high gas production at 45℃ and 60℃. Therefore, it can be concluded that the positive electrode active material in this application can effectively improve the high-temperature performance of alkali metal-ion batteries.

[0078] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this invention, "a plurality of" means at least two, such as two, three, etc., unless otherwise explicitly specified.

[0079] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0080] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.

Claims

1. A positive electrode active material, characterized in that, Includes alkali metal iron manganese phosphates and additives; The additives include metal-organic framework materials and covalent organic framework materials; The alkali metal iron manganese phosphate salt includes at least one of sodium iron manganese phosphate and potassium iron manganese phosphate. The content of the alkali metal iron manganese phosphate in the positive electrode active material is 94wt%~99wt%; The metal-organic framework material is present in the positive electrode active material at a content of 0.5 wt% to 3 wt%. The covalent organic framework material is present in the positive electrode active material at a content of 0.5 wt% to 3 wt%. The metal-organic framework material includes Co6(BPDC)6; The covalent organic framework material includes COF-7; The specific surface area of ​​the metal-organic framework material is >1000 m². 2 / g; The pore size of the metal-organic framework material is 0.8 nm-1.3 nm; The covalent organic framework material has nanopores on its surface, and the pore size of the nanopores is 1.63 nm to 4.80 nm. The D50 particle size of the alkali metal iron manganese phosphate is 1.1 μm to 1.6 μm; The D50 particle size of the metal-organic framework material is 90nm-300nm; The D50 particle size of the covalent organic framework material is 80nm-500nm.

2. The positive electrode active material according to claim 1, characterized in that, The alkali metal iron-manganese phosphate salt has the following chemical formula: MMn a Fe b Al c W d Nb e C f PO4; Where 0 < a < 1, 0 < b < 1, 0 ≤ c < 1, 0 ≤ d < 1, 0 ≤ e < 1, 0 ≤ f < 1, and M is sodium or potassium.

3. A method for preparing a positive electrode active material as described in any one of claims 1 to 2, characterized in that, include: By mixing alkali metal iron-manganese phosphate salts with additives, a positive electrode active material is obtained.

4. The preparation method according to claim 3, characterized in that, The mixing process involves mixing at a speed of 100 rpm to 200 rpm for 1 to 2 hours.

5. A positive electrode plate, characterized in that, include: The positive electrode active material according to any one of claims 1 to 2.

6. An alkali metal ion battery, characterized in that, It includes the positive electrode active material according to any one of claims 1 to 2 or the positive electrode sheet according to claim 5.

7. An electrical device, characterized in that, The positive electrode active material according to any one of claims 1 to 2, the positive electrode sheet according to claim 5, or the alkali metal ion battery according to claim 6.

Citation Information

Patent Citations

  • Crystalline material additives for thick electrodes

    CN117638066A